Real-time assembly of ribonucleoprotein complexes on nascent RNA transcripts - Olivier Duss (Nature Communications, 2018)
The early steps of ribosome assembly occur co-transcriptionally on the nascent ribosomal RNA. Here the authors demonstrate an approach that allows simultaneous monitoring of transcription and ribosomal protein assembly at the single-molecule level in real time.